Commentary on Jones J, Jones KN and Peil J (2018) The impact of the legalization of recreational marijuana on college students. Addictive Behaviors 77: 255–259, https://doi.org/10.1016/j.addbeh.2017.08.015. (February 2019) - Jones, Jacob; Jones, K Nicole
With the broadening legislative changes surrounding legalized recreational marijuana in the United States, tracking the impact of such changes is imperative. As such, in a recent article published in Addictive Behaviors, we identified several emerging trends in the first state to legalize recreational marijuana, Colorado. Since our publication, similar research from other states that have legalized recreational marijuana (Oregon and Washington) has emerged. Here, we attempt to expand on our findings and identify patterns across the research, by comparing and contrasting our results to research in other states with legalized recreational marijuana. We identified several trends including, but not limited to, the rates of marijuana use rising after decriminalization, but not the retail sale of recreational marijuana; recreational marijuana legalization leading to a decrease in the relationship between marijuana and alcohol use; and the identification of binge drinkers as a high-risk population for marijuana use after recreational legalization. We also explore the complicated relationship between marijuana use and academic performance, and point out areas where future research is needed.